123 Myocardial and Fluid Mechanics by Echocardiography Detect Subclinical Changes in Type 2 Diabetes Mellitus. (6th June 2015) - Upton, Ross; Levelt, Eylem; Ariga, Rina; Mahmod, Masliza; Brophy, Carl; Mangual, Jan; Pedrizzetti, Gianni; Clarke, Kieran; Neubauer, Stefan; Leeson, Paul
Abstract : Introduction: Patients with type 2 diabetes mellitus (T2DM) are at increased risk of heart failure and early identification subtle changes may allow preventive interventions. Altered ventricular myocardial and fluid mechanics are early manifestations of cardiac dysfunction and can be quantified by novel echocardiography techniques. Objective: We aimed to assess whether echocardiographic measures of myocardial and fluid mechanics are altered in patients with T2DM. Methods: 34 patients (mean age 54.52 ± 8.3) with uncomplicated T2DM and 22 healthy volunteers (mean age 52.50 ± 12.7) were studied. Echocardiography (Philips ie33) was used to quantify vortex formation time (VFT), a measure of fluid dynamics related to left ventricular geometry and early diastolic mitral flow. 3D datasets were used to quantify axial strain (TomTec) and principal strain (S1), secondary strain (S2) and variability of strain within the myocardium via a dedicated MatLab program. Results: VFT was significantly reduced (p = 0.00003) in patients with T2DM and correlated with the ratio of S1 to S2 (r = 0.45 p = 0.002), consistent with an impact of vortex formation on systolic efficiency (Table 1 ). T2DM was associated with altered myocardial systolic mechanics with reduced S2 (p = 0.004) and increased variability of S1 (p = 0.009) and S2 (p = 0.004) (Figure 1 ). Interobserver variability for measures of VFT, S1 and S2 was low compared with the traditional axial deformation measures. Conclusion: Subclinical changes in myocardial mechanical and ventricular fluid dynamics are identifiable with echocardiography in patients with T2DM. Furthermore, a reduction in VFT is associated with impaired myocardial mechanics.